Efeitos do crescimento pró-pobre e do mercado de trabalho sobre o desequilíbrio regional brasileiro - Manso, Carlos Alberto (2008)
This work aims to contribute to empirical literature on the Brazilian regional disequilibrium analyzing, the period after Real plan stabilization, the economic performance of each region of the country in terms of the growth pro-poor person - economic growth followed by reduction in the inequality - and of the social welfare. Using methodology of Kakwani, Neri and Son (2006), it extracted data of the National Research for Sample of Domiciles (PNAD/IBGE), the present study finds, for each one of the Brazilian’s region: (i) the growth and the inequality of the per capita familiar average income (ii) the evolution of the main indices of poverty (iii) the taxes of growth of the labor income and the corresponding decomposition in tax of job, number of hours worked for person, tax of participation of the labor force and productivity. (iv) the decomposition of the productivity in scholarship, return per year of study and redistribution of this return among the families. Beyond analyzing the regional performances of each one of these items and components, this research quantifies the growth pro-poor person and the social welfare associated to them, contributing, this way, for the agreement on the differences of economic performances among the regions of the country. The results show that the bigger impacts in the income and the social welfare was because of the tax of participation of workers for family and, mainly, to the productivity of them. Regarding to the productivity, it had reduction from 1995 to 2002 and increases from 2003. The increase of the productivity in all Brazilian regions from 2003 was caused by the additions in the average returns proceeding from the education of the workers.